Edible Mushrooms: A Green Biotechnology and Great Nutritional Value for Improving Human Health - Abdel-Aziz, Shadia M.; Hamid, Hoda A.; Fadel, M. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
In recent years, great emergence of environmental issues such as “green biotechnology” or “whitebiotechnology” (in EUR) is developed. Green biotechnology can be regarded as application ofmicroorganisms or their metabolites in food, medicine, and pharmaceutical fields. Edible mushroom is anideal food due to the fairly high content of proteins include amino acids which are essential to human healthand nutrition. Mushroom fungus is easily digested, free of cholesterol, and provides a source of dietaryfiber. Fungal proteins compete successfully with animal protein foods and are healthy alternative to meat.Many studies have found that some species of mushrooms are having therapeutic properties such asantioxidant, antimicrobial, anticancer, cholesterol lowering and immuno-stimulatory effects. Consumptionof mushroom-rich foods is associated with a reduced risk of cardiovascular diseases, and certain types ofcancer. Mushrooms have nutraceutical properties such as prevention or treatment of Parkinson, Alzheimer,hypertension, and high risk of stroke. However, some of wild mushroom are considered to be poisonousand there has been some concern about the concentration of metals such as arsenic, cadmium, copper andlead in wild fungi. Consumption of wild fungi in normal quantities is, however, did not pose any significanthealth risk.